2009
DOI: 10.2337/dc09-0168
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Aliskiren Compared With and in Combination With Irbesartan in Patients With Type 2 Diabetes, Hypertension, and Albuminuria

Abstract: OBJECTIVEWe investigated whether the antiproteinuric effect of the direct renin inhibitor aliskiren is comparable to that of irbesartan and the effect of the combination.RESEARCH DESIGN AND METHODSThis was a double-blind, randomized, crossover trial. After a 1-month washout period, 26 patients with type 2 diabetes, hypertension, and albuminuria (>100 mg/day) were randomly assigned to four 2-month treatment periods in random order with placebo, 300 mg aliskiren once daily, 300 mg irbesartan once daily, or the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 23 publications
(29 reference statements)
4
109
1
2
Order By: Relevance
“…Levels of biomarkers of cardiovascular risk measured in our study were mostly unchanged during aliskiren treatment. This is in agreement with previous short-term studies [5,7]. Of note, aldosterone levels tended to decrease with all doses, which warrants further investigation, since this is a small study and the connection between RAAS blockade (i.e.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Levels of biomarkers of cardiovascular risk measured in our study were mostly unchanged during aliskiren treatment. This is in agreement with previous short-term studies [5,7]. Of note, aldosterone levels tended to decrease with all doses, which warrants further investigation, since this is a small study and the connection between RAAS blockade (i.e.…”
Section: Discussionsupporting
confidence: 80%
“…Several dosage studies [3,4] have demonstrated dosedependent antiproteinuric effects. After the introduction of the renin inhibitor aliskiren and evidence of its antiproteinuric effects [2,5] we aimed to investigate the antiproteinuric effect of increasing doses of aliskiren, by comparing urinary albumin excretion rate (UAER) during placebo and after 2 months of treatment with aliskiren 150 mg, 300 mg or 600 mg once daily. In addition we measured biochemical data of the RAAS and biomarkers of cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…All strategies reduce proteinuria compared with single-agent therapy (5)(6)(7)(8)(9)(10)(11), but hyperkalemia is a risk (12,13). Regimens including an ACE inhibitor and ARB or either drug and DRI are not recommended not only because of the risk of hyperkalemia but also because of renal failure and hypotension, which were seen in large clinical trials (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several animal studies and clinical trials showed the efficacy of this combination on cardiovascular outcomes. 19,[35][36][37][38] The effects of the combination of DRIs and ACEIs or ARBs on post-MI outcomes were investigated in the ASPIRE (Aliskiren Study in Post-MI patients to Reduce rEmodelling) study. 39 In this study, the addition of aliskiren to a standard optimal medical regimen, including an ACEI or an ARB, did not result in benefit with respect to ventricular remodeling compared to placebo and was associated with more adverse events in high-risk post-MI patients with LV Figure 4 Oxidative stress and pro-inflammatory cytokine expression in the heart at 28 days after myocardial infarction (MI).…”
Section: Discussionmentioning
confidence: 99%